Comparative efficacy of Pirfenidone and Meloxicam on early radiotherapy-induced anal sphincter dysfunction in rats - Scripcariu, Dragoș Viorel; Caratașu, Cezar Cătălin; Ciorpac, Mitică; Alexa-Stratulat, Teodora; Szilagyi, Andrei; Buga, Cristian Răzvan; Dobrovăț, Bogdan Ionuţ; Eva, Lucian; Timofte, Andrei Daniel; Lozneanu, Ludmila; Căruntu, Irina-Draga; Iliescu, Radu; et al. (Frontiers in Pharmacology, 2025)
BackgroundRadiation therapy, integral to pelvic tumor management, impacts over half of all cancer patients and may lead to anal sphincter dysfunction due to inflammatory responses and chronic fibrotic remodeling in irradiated tissues. To address this, a targeted animal model has been developed to investigate early post-radiotherapy anal toxicity and evaluates the efficacy of anti-fibrotic and anti-inflammatory agents, Pirfenidone and Meloxicam, as potential treatments against radiotherapy-induced sphincter dysfunction.MethodsThirty male Sprague Dawley rats received a 30Gy dose via stereotactic body radiotherapy targeting the anal canal and sphincter. For 28 days, anal sphincter functionality was assessed using anorectal manometry, involving electrostimulation of the perianal area. Histological evaluations were conducted to qualitatively and quantitatively analyze morphological changes and measure sphincter thickness, providing insights into post-radiation structural integrity.ResultsIrradiated animals exhibited signs of perianal inflammation, without severe complications such as strictures or perforations. Functional assessments showed altered sphincter contractility, with irradiated animals initially displaying increased contraction parameters, which subsequently declined to levels below baseline measurements. The groups treated with Pirfenidone, alone and in combination with Meloxicam exhibited significant improvements in sphincter contractility and showed a notable mitigation in external anal sphincter thickness, concomitant with reduction in collagen deposition and preservation of muscular tissue, compared with untreated irradiated animals.ConclusionThis study demonstrates that Pirfenidone, either as monotherapy or in combination with Meloxicam, mitigates radiation-induced fibrotic remodeling and preserves anal sphincter function. However, the combination therapy did not provide an additive benefit over Pirfenidone alone. These findings highlight Pirfenidone as a promising therapeutic strategy for managing post-radiotherapy sphincter dysfunction. Further research is needed to elucidate the underlying molecular mechanisms and optimize antifibrotic and myoprotective interventions for clinical application in cancer survivors.